Kondisi Jalan Yang Rusak Dampaknya Terhadap Mobilitas Penduduk di Kecamatan Sukaratu Kabupaten Tasikmalaya, Jawa Barat - Soleha, Ika; Nurbahira, Dea Detria (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2024)
This research aims to examine the impact of inadequate roads on hampering population mobility in the Sukaratu District area. Sukaratu District is one of the areas that experiences difficulties in accessing adequate transportation, resulting in limited population mobility. This research was carried out through primary and secondary data collection, including distributing questionnaires and field observations. Data analysis was carried out using a descriptive quantitative approach to understand the impact of roads on population mobility. The results of this research show that inadequate roads in the Sukaratu District area have an impact on hampering population mobility. Potholes, rocky and poorly maintained roads hamper the movement of residents, especially in accessing important facilities such as schools and shopping centers. In this context, improving roads and adequate transportation infrastructure is a necessary solution to increase human mobility in Sukaratu District. Local governments and relevant stakeholders need to work together to identify existing road problems, plan the construction of new roads, and make improvements to existing roads. In this way, it is hoped that population mobility can be increased, local social and economic potential can be developed, and the quality of life of residents in Sukaratu District can improve.